2008
DOI: 10.5194/acp-8-1119-2008
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Intercomparison of ILAS-II version 2 and 1.4 trace species with MIPAS-B measurements

Abstract: (Sweden, 68 • N) at virtually the same location that has been sounded by ILAS-II about 5.5 h prior to the sampling of MIPAS-B. The intercomparison of the new ILAS-II version 2 (Northern Hemispheric sunrise) data to MIPAS-B vertical trace gas profiles shows a good to excellent agreement within the combined error limits for the species O 3 , N 2 O, CH 4 , H 2 O (above 21 km), HNO 3 , ClONO 2 , and CFC-11 (CCl 3 F) in the compared altitude range between 16 and 31 km such that these data appear to be very useful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This is the first comparison with the newest version of the ILAS-II CFC-11 and CFC-12 data (version 3). However, a similar feature has already been seen in comparisons of ILAS-II CFC-11 version 1.4 and version 2 measurements with MIPAS-B (Wetzel et al, 2008). The differences of MIPAS and ILAS-II exceed those of other comparisons by far.…”
Section: Results Cfc-11 V5h: Ilas-iisupporting
confidence: 76%
See 4 more Smart Citations
“…This is the first comparison with the newest version of the ILAS-II CFC-11 and CFC-12 data (version 3). However, a similar feature has already been seen in comparisons of ILAS-II CFC-11 version 1.4 and version 2 measurements with MIPAS-B (Wetzel et al, 2008). The differences of MIPAS and ILAS-II exceed those of other comparisons by far.…”
Section: Results Cfc-11 V5h: Ilas-iisupporting
confidence: 76%
“…15 demonstrates that the combined error of the two instruments (purple line) is far larger than the standard deviation of the differences (brown line), we suspect that the ILAS-II errors are largely overestimated. Above 20 km, Wetzel et al (2008) also found higher mixing ratios. All in all, the agreement of MI-PAS CFC-11 measurements taken during the FR period with those of ILAS-II is not good as it shows far larger differences at the bottom end of the profile than comparisons with, e.g., ACE-FTS or HATS, that are as big as 50 % and also large deviations at the upper end of the profiles that exceed 100 % above 25 km.…”
Section: Results Cfc-11 V5h: Ilas-iimentioning
confidence: 79%
See 3 more Smart Citations